Praktik Service Learning Manajemen Madrasah Diniah Sebagai Laboratorium Sosial Prodi Manajemen Pendidikan Islam STAI Darussalam Nganjuk - Idam Mustofa (Intizam, Jurnal Manajemen Pendidikan Islam, 2019)
The problem of madrasa management is to become a major concern for the Management of Islamic Education Program in STAI Darussalam Nganjuk. Community Service is used for the practice of service learning in madrasa management courses with the Asset-based Community Development (ABCD) approach. Diniah school at the service location were chosen to be a laboratory for capacity building for lecturers so that they can empower their potential in order to respond to changes in regulations and global challenges. A series of activities carried out to empower teachers and students. The results of the activities show the role of the stakeholders of the Al-Qur'an Education Institution in mobilizing its potential and assets in order to increase its capacity. By practicing madrasah management learning service during the live in period, community service can improve student soft skills